Stress detection for visually impaired people using EEG signals based on extracted features from time-frequency domain - Sultana, Samia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2022.